TRAPPING CAPABILITY OF MICROLENS 2D ARRAY BY ACOUSTIC MODULATION - Ho, Quang Quy; Nguyen, Van Thinh; Chu, Van Lanh (JOURNAL OF ADVANCES IN PHYSICS, 2014)
In this article, the microlens 2D array created in acoustic-optical medium by the ultrasonic wave modulation is proposed. The expression described the refractive index induced by cross-interference of two perpendicular ultrasonic waves is approximately derived. By simulation, the 2D array of the Gradedrefractive index lenses are appeared in the thin layer with certain strain-acoutstic constant and thickness. The dependence of focal length and the radius of lens, i.e. its numerical aperture (AN) on thickness and strain constant of layer, and ultrasonic wave intensity are simulated and trapping capability of optical tweezer array is discussed.